Postmemory and intertextuality as devices for (re) construction of the second generation in the narratives of Djaimilia Pereira de Almeida - da Cruz Tavares, Tatiana (2024)
This article analyzes, based on the compositions Esse cabelo (2017) and Luanda, Lisboa, Paraíso (2019), by the Portuguese-Angolan writer Djaimilia Pereira de Almeida, the procedure of post-memory as a relevant device for the (re)construction of narratives of called second generation or children of war. The subjects of this process grew up surrounded by stories, objects and photographs that became a form of post-colonial heritage and helped to form the memory of what was not directly experienced, but was somehow transmitted to them by Family and group memory, that is, post-memory. Therefore, we will cover the trajectories of Mila, Cartola and Aquiles, characters from the mentioned novels, who had their lives transformed by immigration from Angola to Portugal. With this, we aim to bring to light the work of an importante writer from the Angolan diaspora, to evidence how the representation of the historical and subjective experience of post-colonial subjects is carried out and analyze the narrative procedures that are typical of the discourse of memory and post-memory, a term originally proposed by Marianne Hirsch to deal of the transmissions of traumatic episodes or events from one generation to another. Despite being recent, Djaimilia’s work has a substantial critical fortune, therefore, the option to study it based on a concept that is still little explored in her narratives, considering the studies of Marianne Hirsch (2008), Beatriz Sarlo (2007), Margarida Calafate Ribeiro (2013, 2020), António Sousa Ribeiro (2013), among others.